Global tuberculosis report 2018 - Anderson, Laura; Baddeley, Annabel; Dias, Hannah Monica; Floyd, Katherine; García Baena, Inés; Gebreselassie, Nebiat; Gilpin, Christopher; Glaziou, Philippe; Law, Irwin; Nishikiori, Nobuyuki; Rangaka, Molebogeng; Siroka, Andrew; et al. (France : World Health Organization, 2018)
This edition is published in the lead up to the UN high-level meeting on TB. It provides a comprehensive and up-to-date assessment of the TB epidemic, and of progress in the response to the epidemic, at global, regional and country levels. The report is bases primarily on data reported annually to WHO by countries, and databases maintained by other UN agencies and the World Bank
Esta edición se publica antes de la reunión de alto nivel de la ONU sobre TB. Proporciona una evaluación completa y actualizada de la epidemia de TB y del progreso en la respuesta a la epidemia, a nivel mundial, regional y nacional. El informe se basa principalmente en datos reportados anualmente a la OMS por países, y bases de datos mantenidas por otras agencias de la ONU y el Banco Mundial
Contents Abbreviations Acknowledgements Executive Summary Chapter 1. Introduction Chapter 2. Global commitments to end TB and multisectoral accountability Chapter 3. TB disease burden Chapter 4. Diagnosis and treatment: TB, HIV-associated TB and drug-resistant TB Chapter 5. TB prevention services Chapter 6. Financing for TB prevention, diagnosis and treatment Chapter 7. Universal health coverage, social protection and social determinats Chapter 8. TB research and development Annexes 1. The WHO global TB database 2. Country profiles for 30 high TB burden countries 3. Regional and global profiles 4. TB burden estimates, notifications and treatment outcomes
Incluye Contenido
Keywords: INFECCIÓN POR MYCOBACTERIUM; TUBERCULOSIS; TUBERCULOSIS PULMONAR; BACILO DE KOCH; PULMONES -- ENFERMEDADES